2021
DOI: 10.3389/fonc.2021.684941
|View full text |Cite
|
Sign up to set email alerts
|

Combined Impacts of Genetic Variants of Long Non-Coding RNA MALAT1 and the Environmental Carcinogen on the Susceptibility to and Progression of Oral Squamous Cell Carcinoma

Abstract: Oral squamous cell carcinoma (OSCC) is the most common malignant tumor of the oral cavity, and long non-coding (lnc)RNA of metastasis-associated lung adenocarcinoma transcript 1 (MALAT1) was recently reported to play a crucial role in OSCC development and progression. However, potential effects of genetic variants of MALAT1 on the development of OSCC are still unclear. Herein, we performed a case-control study in 1350 patients with OSCC and 1199 healthy controls to evaluate the association between functional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…SNPs of lncRNAs have been proposed to influence certain types of malignancies and angiogenic diseases ( Peng et al, 2017 ; Yuan et al, 2019 ; Weng et al, 2020 ; Ding et al, 2021 ; Wang et al, 2021 ). In previous studies, lncRNA CCAT1 SNP rs67085638 was correlated with the development of gastric cancer ( Olesiński et al, 2021 ), and lncRNA PCAT1 and its SNP rs2632159 were associated with a higher rate of colon cancer, which involves an angiogenesis process ( Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SNPs of lncRNAs have been proposed to influence certain types of malignancies and angiogenic diseases ( Peng et al, 2017 ; Yuan et al, 2019 ; Weng et al, 2020 ; Ding et al, 2021 ; Wang et al, 2021 ). In previous studies, lncRNA CCAT1 SNP rs67085638 was correlated with the development of gastric cancer ( Olesiński et al, 2021 ), and lncRNA PCAT1 and its SNP rs2632159 were associated with a higher rate of colon cancer, which involves an angiogenesis process ( Yang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) are a group of RNAs that could contribute to angiogenesis and cell proliferation in tumor cells ( Su S.-C. et al, 2018 ; Zhao et al, 2020 ; Su et al, 2021b ; Ding et al, 2021 ). Among this group, long intergenic noncoding RNA 00673 (LINC00673) is associated with several malignancies ( Zhu K. et al, 2021 ; Zhu Y. et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the current study, we found that HRH1 was upregulated in OSCC and was correlated with larger tumor sizes and poor prognoses of OSCC patients, suggesting an oncogenic role of HRH1 in OSCC. Previous studies indicated that OSCC is a disease related to multiple gene mutations [ 27 ], and some of the gene polymorphisms were reported to be associated with OSCC risks and progression [ 28 , 29 ]. Although previous reports indicated that HRH1 messenger (m)RNA expression was elevated in subjects with asthma and genetic variants of HRH1 contributed to the risk of allergic asthma [ 30 , 31 ], knowledge of the clinical relevance of HRH1 SNPs in OSCC, which probably result in expression and functional changes of HRH1, is still lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, A total of 10 case-control studies fulfilling the inclusion with 6630 cases and 7457 controls criteria were included in this meta-analysis. The baseline characteristics of these studies are shown in Table 1 [19][20][21][22][25][26][27][28][29][30]. Among them, two studies investigated hepatocellular carcinoma, two studies investigated gastric cancer, two studies investigated colorectal cancer and four studies investigated other cancers (oral squamous cell carcinoma, melanoma, esophageal squamous cell carcinoma, papillary thyroid cancer).…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Peng et al showed that females with a CT genotype of rs3200401 had a lower risk of breast cancer (BC) [18]. Similarly, the subjects with TT genotype were associated with an increased risk of oral squamous cell carcinoma (OSCC) after adjusting for other variables [19]. There is no significant association between rs3200401 C > T and HCC [20,21].…”
Section: Introductionmentioning
confidence: 99%